Characterization of Antibiotic Trimethoprim Adsorption by Granular Activated Carbon - Fauzan Razansyah; Mindriany Syafila; Marisa Handajani (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The presence of antibiotics in aquatic environments has been known to lead to the development of bacteria with resistant genes. One type of antibiotic that has been found in the environment is trimethoprim, necessitating methods to remove this substance from the environment. Adsorption is a process that has been extensively studied in the field of water remediation. This study aims to investigate the adsorption of trimethoprim by granular activated carbon (GAC). Experiments were conducted by creating artificial wastewater containing distilled water and trimethoprim, which was then contacted with the adsorbent with variations in pH and trimethoprim concentration measured periodically up to the 3rd hour. Trimethoprim detection was performed using a UV-Vis spectrophotometer. The contact time required to reach equilibrium increased with the initial concentration of trimethoprim. The variations in initial trimethoprim concentrations of 5, 10, 20, 35, and 50 mg/L reached adsorption equilibrium after a contact time of 180 minutes with a GAC mass of 3 grams. All the percentages of trimethoprim removal after the contact time of 180 minutes at various concentrations used in this study were above 98%. The pH level has been proven to affect the trimethoprim removal process. The pseudo-second-order kinetic model has a high correlation with the adsorption process of trimethoprim by GAC. The isotherm model suitable for the interaction between trimethoprim and GAC was the Freundlich model.